2014
DOI: 10.5216/ag.v8i1.22126
|View full text |Cite
|
Sign up to set email alerts
|

Distribuição Da Frequência Mensal Da Precipitação Para Região Oeste De Goiás: Comparação Entre Dois Postos Pluviométricos

Abstract: Distribuição da frequência mensal da precipitação para região Oeste de Goiás: comparação entre dois postos pluviométricosDistribution rate monthly precipitation to the region from West Goiás: comparison between two stations pluviometric

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
1
0
1
Order By: Relevance
“…Rainfall is one of the essential elements in tropical regions since it, directly and indirectly, influences human activities, the economy, and the environment. In this sense, accurate knowledge of the characteristics of this variable is of fundamental importance for planning and monitoring the impacts caused by excess or scarcity of rainfall [10,78]. Considering the spatial distribution of average annual rainfall in the state of Pernambuco from 1990 to 2020, it was found that, in quantitative terms, the highest rainfall rates were concentrated in the Metropolitana do Recife, and Zona da Mata mesoregions, followed by the Agreste mesoregions of Sertão Pernambucano and Sertão do São Francisco.…”
Section: Discussionmentioning
confidence: 99%
“…Rainfall is one of the essential elements in tropical regions since it, directly and indirectly, influences human activities, the economy, and the environment. In this sense, accurate knowledge of the characteristics of this variable is of fundamental importance for planning and monitoring the impacts caused by excess or scarcity of rainfall [10,78]. Considering the spatial distribution of average annual rainfall in the state of Pernambuco from 1990 to 2020, it was found that, in quantitative terms, the highest rainfall rates were concentrated in the Metropolitana do Recife, and Zona da Mata mesoregions, followed by the Agreste mesoregions of Sertão Pernambucano and Sertão do São Francisco.…”
Section: Discussionmentioning
confidence: 99%
“…A precipitação pluviométrica constitui, entre os elementos atmosféricos, o que apresenta maior interesse da sociedade. O conhecimento do comportamento da precipitação pluviométrica ao longo do tempo é imprescindível para o monitoramento dos impactos causados pelo excesso ou pela falta prolongada de chuva e contribui para o desenvolvimento de uma série de atividades, tanto nas áreas urbanas, quanto nas rurais (SPECIAN e VECCHIA, 2014;NUNES et al, 2016).…”
Section: Introductionunclassified